Implementation of a long range-based monitoring system for environmental remote safety schemes - Mahmood Jalal Ahmad Alsammarraie; Adnan Hussein Ali; Aqeel A. Al-Hilali; Hind Q. Mohammad Monir; Mohannad Sameer Jabbar; Haitham Bashar Qasim (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The effects of poor air quality on people are profound. Air pollution and health issues are linked to millions of deaths. The World Health Organization (WHO)and the environmental protection agency (EPA)have produced several regulations and guidelines to control and enhanceair quality. Several authors have recently suggested low-cost tools for instantly assessing air quality. the abundance of inexpensive ways to assess air quality and collect sensor data. The design and employment of remote safety monitoring for humidity, temperature, and carbon monoxide has been merged into a single tool in this work. The results findings can be observed on the actual measured instrument’s organic light-emitting diode (OLED)show and the liquid crystal display (LCD)remote monitoring system. This device uses ESP32 microcontroller with long range (LoRa)wireless communication technology.The DHT22 sensor is used to detect humidity and temperature, while the MQ-7 sensor is used to monitor carbon monoxide levels. Testing measurements are calibrated using instruments that meet industrial standards (AS8700A CO meter and 4,000 NV weather tracker) used in environmental station. If the abnormalities in the recorded parameters are detected, then alert will be triggered. This instrument can help patients and workers to check their surroundings and provide remote monitoring to health service providers.